Enhanced depth imaging optical coherence tomography and fundus autofluorescence findings in bilateral choroidal osteoma: a case report - Erol,Muhammet Kazim (2013)
The authors present enhanced depth imaging optical coherence tomography (EDI OCT) and fundus autofluorescence (FAF) characteristics of a patient with bilateral choroidal osteoma and try to make a correlation between two imaging techniques. Two eyes of a patient with choroidal osteoma underwent complete ophthalmic examination. Enhanced depth imaging optical coherence tomography revealed a cage-like pattern, which corresponded to the calcified region of the tumor. Fundus autofluorescence imaging of the same area showed slight hyperautofluorescence. Three different reflectivity patterns in the decalcified area were defined. In the areas of subretinal fluid, outer segment elongations similar to central serous chorioretinopathy were observed. Hyperautofluorescent spots were evident in fundus autofluorescence in the same area. Calcified and decalcified portions of choroidal osteoma as well as the atrophy of choriocapillaris demonstrated different patterns with enhanced depth imaging and fundus autofluorescence imaging. Both techniques were found to be beneficial in the diagnosis and follow-up of choroidal osteoma.